2015
DOI: 10.1107/s160057751500301x
|View full text |Cite
|
Sign up to set email alerts
|

The Soft X-ray Research instrument at the Linac Coherent Light Source

Abstract: The Soft X-ray Research instrument provides intense ultrashort X-ray pulses in the energy range 280-2000 eV. A diverse set of experimental stations may be installed to investigate a broad range of scientific topics such as ultrafast chemistry, highly correlated materials, magnetism, surface science, and matter under extreme conditions. A brief description of the main instrument components will be given, followed by some selected scientific highlights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Experiment was performed at the linac coherent light source (LCLS) soft x-ray materials science (SXR) instrument [42,43] with the liquid jet endsation [44]. The 1 mol l −1 Fe(CO) 5 ethanol solution was photo-excited at 266 nm (4.66 eV).…”
Section: Methodsmentioning
confidence: 99%
“…Experiment was performed at the linac coherent light source (LCLS) soft x-ray materials science (SXR) instrument [42,43] with the liquid jet endsation [44]. The 1 mol l −1 Fe(CO) 5 ethanol solution was photo-excited at 266 nm (4.66 eV).…”
Section: Methodsmentioning
confidence: 99%
“…Data collection of the partial fluorescence yield (PFY) measurements were performed at the SXR instrument at the LCLS [29][30][31][32][33]35] as described by Mitzner et al in [24]. A schematic drawing of the set up including the self-seeding scheme of the FEL is depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Soft x-ray L-and K-edge XAS in the 250-1000 eV range typically require a spectral resolution corresponding to 0.05%, hence the beam has to be passed through a grating monochomator (~20% reflectivity) with a bandwidth-narrowing exit slit, although it has been shown that at ~100 eV experiments without an exit slit can be performed [28]. As a consequence of these and related losses in typical soft x-ray beamlines, the monochromatic peak flux on the sample at the soft x-ray endstation (SXR) of LCLS is reduced to a few percent of the original peak flux depending on the selected resolving power [29][30][31][32][33]. This reduced monochromatic photon flux is a limitation in particular for L-edge absorption spectroscopy of 3d transition metal atoms for dilute samples such as metalloenzymes (~mM) and for more complex techniques that require a particularly high average flux such as inelastic x-ray scattering (RIXS) measurements that hold great potential for quantitative electronic structure analyses [4].…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was performed at the Soft X-ray Material Science (SXR) Instrument of the Linac Coherent Light Source (LCLS) [25][26][27]. The x-ray beam in self-amplified spontaneous emission (SASE) mode, which have an energy bandwidth of ~ 0.3 %, was set in the photon energy range between 1480 and 1510 eV, which lies well below the K-edge of aluminum.…”
Section: Introductionmentioning
confidence: 99%